Subcutaneous Enoxaparin Safely Facilitates Bedside Sustained Low-Efficiency Hemodialysis in Hypercoagulopathic Coronavirus Disease 2019 Patients—A Proof-of-Principle Trial - Neumann-Haefelin, Elke (Crit Care Explor, 2020)
OBJECTIVES: Renal replacement therapy in coronavirus disease 2019 patients is complicated by increased activation of the coagulation system. This may worsen the quality of hemodialysis and contribute to a shortage of dialysis machines as well as plastic disposables during the pandemic. This study describes a simple and safe protocol of anticoagulation with low-molecular-weight heparin in combination with bedside sustained low-efficiency hemodialysis in coronavirus disease 2019 patients. DESIGN: Monocentric observational cross-over trial investigating sustained low-efficiency hemodialysis with unfractionated heparin following sustained low-efficiency hemodialysis with low-molecular-weight heparin. SETTING: Coronavirus disease 2019-ICU in a German Tertiary Care University Hospital. PATIENTS: Three consecutive severe coronavirus disease 2019 patients receiving nine sustained low-efficiency hemodialysis therapies with unfractionated heparin followed by 18 sustained low-efficiency hemodialysis therapies with low-molecular-weight heparin. INTERVENTIONS: Switch from IV unfractionated heparin to subcutaneous low-molecular-weight heparin enoxaparin in therapeutic doses for patients receiving bedside sustained low-efficiency hemodialysis. MEASUREMENTS AND MAIN RESULTS: Nine renal replacement therapy sessions in patients anticoagulated with high doses of unfractionated heparin had to be discontinuated prematurely because of clotting of tubes or membrane and poor quality of hemodialysis. In the same patients, the switch to anticoagulation with therapeutic doses of the low-molecular-weight heparin enoxaparin allowed undisturbed bedside sustained low-efficiency hemodialysis for at least 12 hours. Quality of hemodialysis was excellent, no bleeding event was observed. CONCLUSIONS: Systemic anticoagulation with subcutaneous enoxaparin provides an effective and safe renal replacement procedure in critically ill patients with coronavirus disease 2019 and hypercoagulability. The protocol reduces the risk of filter clotting, blood loss, and poor dialysis quality and may also prevent systemic thromboembolism.